2017
DOI: 10.1002/ijc.30543
|View full text |Cite
|
Sign up to set email alerts
|

Transient immunological and clinical effectiveness of treating mice bearing premalignant oral lesions with PD‐1 antibodies

Abstract: A carcinogen‐induced premalignant oral lesion model that progresses to oral cancer was used to examine the impact of blocking PD‐1 on cytokine expression and on progression of lesions to cancer. The results of this study show increased production of IL‐2 and the inflammatory cytokines IL‐6, IL‐17 and TNF‐α by spleen cells of lesion‐bearing mice that were treated with PD‐1 antibody for 1 week compared to cytokine production by spleen cells of lesion‐bearing mice treated with control antibody. Production of IFN‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 46 publications
3
14
1
Order By: Relevance
“…The present study also confirmed our prior results demonstrating that PD-1 treatment caused an early, but transient, increase in spleen cell production of Th1 and inflammatory cytokines which was seen after 1 week of PD-1 antibody treatment and declined thereafter [29]. The exception was IFN-γ, which peaked after 3 weeks of treatment before declining.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study also confirmed our prior results demonstrating that PD-1 treatment caused an early, but transient, increase in spleen cell production of Th1 and inflammatory cytokines which was seen after 1 week of PD-1 antibody treatment and declined thereafter [29]. The exception was IFN-γ, which peaked after 3 weeks of treatment before declining.…”
Section: Discussionsupporting
confidence: 92%
“…These results for IFN-γ contrasted with results for lymph node secretion of the inflammatory mediators IL-17 or TNF-α in response to a lesion or cancer challenge, which was greater for control antibody-treated mice. The responses of lymph node cells to lesion or HNSCC lysate challenges were transient, which is consistent with what we previously demonstrated for spleen cell responses to challenge [29]. It is also consistent with the transient increase in levels of cytokines within tongue tissue of PD-1 antibody-treated mice and with the transient increase in spontaneous spleen cell secretion of cytokines.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…GM-CSF has shown to be increased in T lymphocytes after nerve injury [17] and when injected directly into the skin results in nociceptive behavior [61]. However, because TNFα was identified as a primary mediator upregulated with anti-PD-1/PD-L1 therapy [13,41], we will focus on TNFα for subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…This therapeutic tactic has shown promise for oral cancers [9,41,79]. Inhibition of the PD-1/PD-L1 pathway using monoclonal antibodies enhances leukocyte infiltration and increases tumor necrosis factor alpha (TNFα) secretion into the oral cancer microenvironment [42].…”
Section: Introductionmentioning
confidence: 99%